Corneal Transplantation - Ghaem maghami A (Iran University of Medical Sciences, 1994)
ExtractDefective corneas are the leading cause of blindness world wide and the second leading cause, after diabetic retinopathy,of blindness in the united state , afflicting 30000 americans each year. happily, nearly 95 percent of those who have corneal transplantations( in 1985 they numbered,26300) regain their sight. The cornea is a transparent, a vascular, dim-sized tissue continious with the white sclera of the eye. It acts asa refractive and protective membrane or " Window" through which light passes to the retina.injury , infection,congenital defects,or various corneal degenerations can scar, cloud,or change the shape of the cornea, blocking light rays and,thus, vision.